12.5.13 Pneumatic Circuit For Fully Automat - M.Galal Rabie (McGraw-Hill's AccessEngineering., 2024)
Fully Automatic Control of a Double-Acting Cylinder. The operation starts by manually actuating a 3/2 directional valve with mechanical position locking. This action actuates a bi-stable 5/2 directional control valve. The reciprocating motion of cylinder continues until the manually operated valve is returned back.